YIELD OF CORN GRANTS IRRIGATED BY UNDERGROUND DRIPPING AND ESTIMATION OF IRRIGATION WITH TIME FORECAST DATA - de Oliveira, Z. B. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The objective of the present work was to evaluate the yield of grains of drip irrigated maize installed at two depths and two spacings between rows and to compare the irrigations performed with measured meteorological data with irrigations estimated using data from the weather forecast. The work was carried out in the agricultural year 2013/14 in Júlio de Castilhos-RS, in three stages: a field for the analysis of cultural data, one for the estimation of ETo with data of the weather forecast (ETo prev) and one for the estimate of the need for irrigation from ETo prev and ETo calculated with measured meteorological data (ETo). Estimates of ETo, ETo prev and the need for irrigation followed the recommendations of the FAO - 56 bulletin. The highest grain yield (1, 1895.34 kg ha - 1) was observed using tubers installed 40 cm deep. The mean square error (RMSE) of ETo predicted in comparison to ETo was 1.05 mm dia-1, indicating a good agreement between estimated values and observed values. The number of recommended irrigations with ETo and ETo prev was the same (8 irrigations), showing that the use of weather forecast data for irrigation management may be an alternative to locations where measured meteorological data are unavailable.